Gray Patch Tinea Capitis by Microsporum canis in a Child: A Case Report Highlighting Environmental Risk Factors and Diagnostic Nuances - Mario Korwa; Luh Made Mas Rusyati; Handelia Phinari; Andrew Wicaksono; Nandya Dwizella (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Tinea capitis, a dermatophytosis of the scalp, is a leading cause of hair loss in children. Its successful management hinges on understanding its complex etiology, including host susceptibility and pathogen virulence. Microsporum canis, a zoophilic fungus, is a primary causative agent, yet its transmission pathways and diagnostic markers are not fully elucidated. Case presentation: A 3-year-old female presented with a two-week history of progressive, pruritic alopecia. Clinical history was notable for the absence of animal contact but revealed significant environmental exposure at a hair salon. Dermatological examination showed multiple, well-demarcated, alopecic patches with fine scaling, characteristic of gray patch tinea capitis. While Wood's lamp examination was negative, trichoscopy revealed comma hairs and Morse code-like hairs, suggesting fungal infection. Microscopic examination of hair shafts confirmed an ectothrix invasion pattern, and fungal culture definitively identified Microsporum canis. The patient achieved complete resolution following a six-week course of oral griseofulvin and adjuvant topical ketoconazole. Conclusion: This case demonstrates that indirect fomite transmission from environmental reservoirs like hair salons is a critical risk factor for zoophilic tinea capitis, independent of animal contact. It further establishes trichoscopy as an essential tool for accurate, rapid diagnosis when classic signs, such as Wood's lamp fluorescence, are absent, thereby optimizing patient management and public health outcomes.